Adult onset hemophagocytic lymphohistiocytosis prognosis is affected by underlying disease and coexisting viral infection: analysis of a single institution series of 35 patients. Issue 4 (3rd June 2016) - Cattaneo, Chiara; Oberti, Margherita; Skert, Cristina; Passi, Angela; Farina, Mirko; Re, Alessandro; Tozzi, Paola; Borlenghi, Erika; Rossi, Giuseppe
Abstract: Adult onset hemophagocytic lymphohistiocytosis (HLH) is a hyperinflammatory syndrome, which can develop as a complication of many disorders. Early diagnosis is essential in order to avoid a fatal outcome. To confirm the diagnosis of acquired HLH made in a single institution series of adult patients with HLH‐04 criteria, we applied the HScore and evaluated prognostic factors associated with clinical outcome. The median age of 35 patients was 54 (range 17–81), M/F ratio was 20/15. In 26/35 (74.3%) patients, an underlying haematological disease was present (2 Multicentric Castleman Disease, 10 B‐cell Non‐Hodgkin Lymphoma [NHL] and 14 T/NK‐cell NHL); an autoimmune disorder was observed in four (11.4%) patients (one Still Disease, one undifferentiated connective tissue disease and two haemolytic anaemia); in five (14.3%), no underlying disease was identified. A concomitant infection by EBV was observed in 10 patients (28.6%), CMV in 8 (22.9%), HHV8 in 6 (17.1%) and HIV in 1 (2.9%). Hyperferritinemia, fever and splenomegaly were present in more than 90% of patients, whereas bone marrow hemophagocytosis in 51% of cases only. According to HScore, 34/35 patients had a >75% and 32/35 >93% probability of HLH. Four‐year overall survival and HLH‐free survival were 17.8% (CI 1.9–33.8) and 23.8% (CI 7.3–40.3), respectively. By multivariate analysis, presence of oedema and hyperbilirubinemia were predictors of death, whereas there was a statistically significant trend for viral infection as predictor of poor prognosis. B‐NHL diagnosis was confirmed as associated to a better prognosis in comparison with T/NK lymphoma (4‐year HFS 53.3% vs. 0%, p = 0.09) and similar to other aetiologies. Copyright © 2016 John Wiley & Sons, Ltd.